Anticonvulsant and related neuropharmacological effects of a hydro-ethanolic whole plant extract of synedrella nodiflora (L.) gaertn (FAM:Asteraceae). - Amoateng, Patrick (2011)
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy on February, 2011.